Electrokinetic remediation of nickel from low permeability soil - Saleem, Muhammad; Chakrabarti, Mohammed Harun; Irfan, M.F.; Hajimolana, Sayed Ahmad; Hussain, Mohd Azlan; Hasan, Diya'uddeen Basheer; Daud, Wan Mohd Ashri Wan (Electrochemical Science Group, 2011)
Electrokinetic remediation of nickel from low permeability soil using titanium electrodes having inter-electrode spacing of 10 cm was carried out in a cylindrical reactor. The influences of current density, voltage gradient and electrolyte pH were investigated upon removal efficiency for 60 h experimental runs. Efficiency improved from 49.3 to 57.2 when the current density was increased from 4.36 mA/cm 2 to 13.1 mA/cm 2. Furthermore, an enhancement in efficiency from 38.5 to 54.3 was observed when voltage gradient increased from 1 V/cm to 2 V/cm (at 13.1 mA/cm 2). Further increase in voltage gradient to 2.5 V/cm improved efficiency during initial runs. However, an overall reduction of 3.2 was observed after 60 h of operation in comparison to that obtained at 2 V/cm. This may be attributed to precipitation and localized accumulation of metallic ions. An inverse relationship between efficiency and electrolyte pH was also observed (at 13.1 mA/cm 2 and 2 V/cm). Although a removal of 74.1 was achieved at pH = 4.5, the system required optimization as the nickel content in treated soil was above the maximum values given in international standards.